Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1017/s0950268815000552
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofClostridium difficileinfection: results of a hospital-based study in Krakow, Poland

Abstract: Over the past two decades Clostridium difficile infection (CDI) has appeared as a major public health threat. We performed a retrospective study based on the records of patients hospitalized for CDI at the University Hospital in Krakow, Poland, between 2008 and 2014. In the study period, CDI occurred in 1009 individuals. There were 790 (78%) individuals who developed infection only once, whereas 219 (22%) developed infection more than once. The percentage of deaths within 14 days of CDI confirmation was 2·4%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 46 publications
2
27
0
3
Order By: Relevance
“…Nonetheless, a significant proportion of CDI occurs in a younger population. Age > 65 years is a significant risk factor not only for CDI itself, but also for poor clinical outcome including severity and mortality [ 3 , 7 ]. Although most cases of CDI are linked to healthcare exposure, either hospitalization or nursing home stay, recent studies suggest that the incidence of community-acquired CDI is growing, and might have recently reached up to 30% of all CDI cases [ 8 ].…”
Section: Risk Factors Associated With CDImentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, a significant proportion of CDI occurs in a younger population. Age > 65 years is a significant risk factor not only for CDI itself, but also for poor clinical outcome including severity and mortality [ 3 , 7 ]. Although most cases of CDI are linked to healthcare exposure, either hospitalization or nursing home stay, recent studies suggest that the incidence of community-acquired CDI is growing, and might have recently reached up to 30% of all CDI cases [ 8 ].…”
Section: Risk Factors Associated With CDImentioning
confidence: 99%
“…Mortality rate directly due to CDI is estimated at 5%, whereas mortality associated with CDI complications reaches 15–25%, and up to 34% in intensive care units (ICU). Mortality doubles in ICU patients with CDI, as compared with ICU patients without CDI [ 7 , 48 , 49 ]. Poor outcome is associated with older age, high leukocytosis, hypoalbuminemia, and high creatinine level [ 43 , 50 ].…”
Section: Clinical Manifestationmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the USA and Europe indicate a range from 10 to up to 90 cases of CDI per 10,000 hospitalizations annually [34]. Research conducted at the University Hospital in Kraków, Poland, in 2008-2014 showed that over 2/3 of patients diagnosed with C. difficile were infected during their stay in hospital [35]. Reports on the incidence rate of infectious diseases, infections and poisoning in Poland (Polish: Raporty ws.…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%
“…Particular attention should be paid to critically ill patients who are at increased risk of developing diarrhoea. The disease makes treatment difficult, prolongs hospitalisation, but also exposes the patient to serious complications [21][22][23].…”
Section: Risk Factorsmentioning
confidence: 99%